Spremljanje skladnosti uporabe protimikrobnih zdravil pri okužbah sečil s smernicami v Splošni bolnišnici Jesenice - Mavsar-Najdenov, Brigita (Farmacevtski vestnik, 2011)
Urinary tract infections (UTI) are among the most common problems of patients in general practice as well as in hospitals, where they represent about one third of nosocomial infections. Increasing resistance of Escherichia coli, themost common cause of UTI, to the commonly used antimicrobials trimethoprim with sulfametoxazole and fluoroquinolones, requires a rational use of these drugs. In most admitted patients with infections, there is necessary to start antimicrobial treatment before getting results of microbiological testing. To start most appropriate empirical antimicrobial treatment, physicians are supported with guidelines of Chemoterapeutic Society of the Slovenian Medical Association and Slovenian Society of Nephrology.
Keywords: okužbe sečil; protimikrobna zdravila; smernice; therapy; zdravljenje